Competition law enforcement in Hong Kong SAR and in Ireland: similar and atypical. Issue 2 (17th June 2019) - Lucey, Mary Catherine
Abstract : Purpose: This paper aims to understand the emergence, operation and evolution of judge-centred models for the enforcement of competition law in Ireland and in Hong Kong SAR. The public enforcement model in Hong Kong chimes with the Irish regime where competence to adjudicate on competition law violations and to impose sanctions is intentionally reserved exclusively to judges. This design choice renders the Irish and Hong Kong regimes both similar to each other and atypical on the global stage, where in many jurisdictions an administrative competition agency investigates suspected infringements, makes determinations of infringements and may penalise infringers. Design/methodology/approach: This paper starts by detailing the current competition law architecture in each jurisdiction. Then, it examines closely the discourse (expressed in consultations, experts' reports and Parliamentary documents) in the lengthy period preceding their introduction. This approach aims, firstly, to understand why judicial models were chosen over more familiar administrative ones and, secondly, to unearth any similar concerns which had a bearing on the choice of atypical design. Next, it analyses some implications of the judicial model in operation for, firstly, parties; secondly, the administrative competition agencies; and, thirdly, the evolution of competition law. Findings: It finds the existence of similar concerns surrounding due process/separation of power arose in each jurisdiction. Other similar strands include a sluggish political appetite which delayed reform. Each jurisdiction actively sought to inform itself about international experience but did not feel obliged to copy the enforcement dimension even where substantive prohibitions were persuasive. Research limitations/implications: It shines a light on the independent response by two small Common Law jurisdictions, which does not converge with popular administrative international models of competition law enforcement. Practical implications: It is hoped that the decades-long experience in Ireland may interest those involved in Hong Kong competition law, which is at a comparatively fledgling stage of development. Originality/value: This is an original research and appears to be the first paper exploring the atypical approaches taken in Hong Kong SAR and Ireland to designing locally suited regimes for the enforcement of competition law.